Biofilm Forming Bacteria during Thermal Water Reinjection. (9th January 2017) - Osvald, Máté; Maróti, Gergely; Pap, Bernadett; Szanyi, János
Abstract : Reinjection of heat-depleted thermal water has long been in the center of scientific interest in Hungary regarding around 1000 operating thermal wells. While the physical and chemical aspects of reinjection have partly been answered in the past years, the effects of biological processes are still less known. We carried out our investigations in the surface elements of the Hódmezővásárhely geothermal system which is one of the oldest operating geothermal systems in Hungary. About one-third of the used geothermal water has been reinjected since 1998 by two reinjection wells at the end of the thermal loops. During the operation, plugging of the surface system was experienced within a few-day-long period, due to biological processes. The goal of our research was to find the dominant species of the microbial flora and to make a proposal to avoid further bacterial problems. We found that the reinjected, therefore the produced, water's chemical oxygen demand, phenol index, and BTEX composition basically determine the appearing flora on the surface. When the concentration of these compounds in the thermal water is significant and residence time is long enough in the buffer tank, certain bacteria can be much more dominant than others, thus able to form a biofilm which plugs the surface equipment much more than it is expected.